2022
DOI: 10.3390/jcm11051154
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Drug Interactions with Cannabis: A Systematic Review

Abstract: Concomitant use of cannabis with other drugs may lead to cannabis–drug interactions, mainly due to the pharmacokinetic mechanism involving the family of CYP450 isoenzymes. This narrative systematic review aimed to systematize the available information regarding clinical relevance of cannabis–drug interactions. We utilized the PubMed/Medline database for this systematic review, using the terms drug interactions and cannabis, between June 2011 and June 2021. Articles with cannabis–drug interactions in humans, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 46 publications
1
46
0
1
Order By: Relevance
“…This phenomenon has been reported before, but only where activity of CYP1A2 was lower than expected 3 . Our patient had normal CYP1A2 activity and was a smoker of tobacco and cannabis (the latter only when not hospitalized)—both CYP1A2 inducers 14 …”
Section: Discussionsupporting
confidence: 82%
“…This phenomenon has been reported before, but only where activity of CYP1A2 was lower than expected 3 . Our patient had normal CYP1A2 activity and was a smoker of tobacco and cannabis (the latter only when not hospitalized)—both CYP1A2 inducers 14 …”
Section: Discussionsupporting
confidence: 82%
“…CBD can be involved in strong drug interactions mediated by CYP2C9, 2C19, and 3A and moderate drug interactions mediated by CYP1A2 and 2D6. THC may participate in strong CYP2C9 and weak CYP1A2 and 3A mediated drug interactions [ 282 , 283 , 284 ]. For example, the oral administration of CBD with the anticonvulsant clobazam led to a significant increase in the plasma concentrations and AUC of its active metabolite N-desmethylclobazam, which is metabolized predominantly by CYP2C19 [ 285 , 286 , 287 ].…”
Section: Pharmacogenomics Of Metabolismmentioning
confidence: 99%
“…Studies have reported that vaporized cannabis increased the analgesic effect of morphine and oxycodone without producing significant differences in the AUC of the medications in patients with chronic pain [ 293 , 294 ]. It was suggested that there is a pharmacodynamic interaction between the opioids and cannabinoids, which most probably involve altered interactions with receptors [ 284 ]. All drug–drug interactions are complex; however, genetic variations can make the DDIs even more problematic and risky.…”
Section: Pharmacogenomics Of Metabolismmentioning
confidence: 99%
“…There are limited data on clinically significant drug interactions related to cannabis use 71 . Several case reports have been published describing an interaction between cannabis warfarin leading to a supratherapeutic international normalized ratio and resulting in one significant bleeding event 75 . Patients taking warfarin should be advised to abstain from cannabis use.…”
Section: The Pharmacist's Approach To the Patient Using Cannabismentioning
confidence: 99%